2013
DOI: 10.1016/j.cub.2012.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Centrosomal PP1 by NIMA Kinase Unlocks the MPF Feedback Loop to Promote Mitotic Commitment in S. pombe

Abstract: PP1 recruitment to Cut12 sets a threshold for Polo's feedback-loop activity that locks the cell in interphase until Cdc25 pushes MPF activity through this barrier to initiate mitosis. We propose that events on the SPB (and, by inference, the centrosome) integrate inputs from diverse signaling networks to generate a coherent decision to divide that is appropriate for the particular environmental context of each cell. PP1 recruitment sets one or more critical thresholds for single or multiple local events within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 48 publications
3
63
0
2
Order By: Relevance
“…The direct correlation between the degree of PP1 recruitment to Cut12 and the level of Polo Plo1 activity detected in whole cell extracts established that a primary impact of PP1 recruitment to Cut12 is to set the level of Polo Plo1 activity throughout the cell (Mulvihill et al 1999;MacIver et al 2003;Grallert et al 2013a). PP1 recruitment to Cut12 also sets local Polo Plo1 activity at each individual SPB so that the temperature-sensitive loss-of-function cut12.1 mutation that enhances PP1 affinity for Cut12 blocks the conversion of the new SPB into a mitotic pole (Bridge et al 1998;MacIver et al 2003;Tallada et al 2009;Grallert et al 2013a). Consequently, cells form monopolar rather than bipolar spindles and cells die.…”
Section: The Centrosome and Spb As Control Centersmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct correlation between the degree of PP1 recruitment to Cut12 and the level of Polo Plo1 activity detected in whole cell extracts established that a primary impact of PP1 recruitment to Cut12 is to set the level of Polo Plo1 activity throughout the cell (Mulvihill et al 1999;MacIver et al 2003;Grallert et al 2013a). PP1 recruitment to Cut12 also sets local Polo Plo1 activity at each individual SPB so that the temperature-sensitive loss-of-function cut12.1 mutation that enhances PP1 affinity for Cut12 blocks the conversion of the new SPB into a mitotic pole (Bridge et al 1998;MacIver et al 2003;Tallada et al 2009;Grallert et al 2013a). Consequently, cells form monopolar rather than bipolar spindles and cells die.…”
Section: The Centrosome and Spb As Control Centersmentioning
confidence: 99%
“…This glycine/valine switch reduced PP1 recruitment to Cut12 leading to the revelation that a complete block to PP1 recruitment to Cut12 enabled cells to survive the otherwise lethal abolition of Cdc25 function (Grallert et al 2013a). Thus, PP1 recruitment to Cut12 is integral to the mitotic commitment switch.…”
Section: The Centrosome and Spb As Control Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that Cut12 mutations mapped to a conserved motif implicated in the recruitment of protein phosphatase 1 (PP1). Mutation of this PP1 docking site in Cut12 decreased not only the affinity of PP1 for Cut12, but also advanced the localization of active Plo1 to SPBs [52]. This implies that PP1 association with Cut12 normally delays Plo1 localization to SPBs, presumably by interfering with a direct association between Plo1 and Cut12 (figure 2b) [51].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of these residues by Cdk1/cyclin B and Fin1, a kinase of the never in mitosis (NIMA) family, disrupted the association of PP1 with Cut12. As these phosphorylations occur late in G2 phase, this allows the recruitment of active Plo1 to SPBs and initial activation of SPB-associated Cdk1/cyclin B at the right time (figure 2c) [52]. This attractive model for the spatial control of Cdk1/cyclin B activation was confirmed by elegant re-targeting experiments demonstrating that activation of Cdk1/cyclin B or Plo1 at the SPB, but not at any other location, is sufficient to commit cells to mitotic entry [53].…”
Section: Introductionmentioning
confidence: 99%